Analyzing Machine learning Algorithm for Predicting an Accuracy of Meteorological Data - Manikandan, M; Mala, R (International Journal of Computer Sciences and Engineering, 2025)
Meteorological data analysis in the form of data mining is concerned to predict the knowledge of weather condition. To make an accurate prediction is one of the challenging of meteorologist to survey the weather condition efficiently. Decision tree algorithms are suitable for analyzing the data of meteorological behavior. By evaluates three algorithm of decision tree such as Random Forest, C4.5, C4.5 with Bootstrap aggregation, to analyse the time efficiency and accuracy of classification. These accuracy of algorithm when it operates on trained weather data of selected location. Those locations are selected through monsoon condition based on India country